Employment of university students in China and abroad: A systematic literature review - Zhang, Ziran; Hasan, Ahmad (NUN Gemilang ENT., 2024)
At present, the phenomenon of "employment difficulty" among university students is relatively common. In the past, the academic circle has conducted in-depth research on the employment of university students, and this paper studies research done by Chinese and foreign scholars on the employment of university students. This article is a preliminary study based on literature highlights, readings, inquiries, and views using library resources including circulars, books, journals, and websites. The preliminary survey results indicate that basic theoretical research and assessment methods, both in China and abroad, are relatively mature and have yielded rich results. However, it should be noted that there are still many important problems to be solved, and there is still a large space for deepening and expanding. First, socialism with Chinese characteristics has entered a new era, putting forward new requirements for university students. So, what is the new connotation of university students' employment views? At present, the research in this area is still unknown. Second, scholars rarely focus on a certain discipline when they study the employment issues of university students. Thirdly, when evaluating the effects of students' employment notions on future employment, research frequently focuses on graduates rather than current students. Finally, very few academics examine it from the standpoint of international relations.